2019
DOI: 10.1016/j.chempr.2019.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Acidic Stability of Zeolitic Imidazolate Frameworks by Biofunctional Molecules

Abstract: We demonstrate the presence of a symbiotic stability reinforcement effect between bioentities and crystalline ZIFs, where the ZIF protects biomolecules from denaturation and the biomolecules improve the acid resistance of the ZIF framework. The strategy provides a potential route for stabilizing MOFs for diverse technological and industrial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
148
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 52 publications
5
148
0
Order By: Relevance
“…Our study revealed that there exists an exclusive synergistic stability effect of both the biomolecule guest and MOF host, enabled from the unique, new coordination bonds between the host and guest molecules ( Fig. 4C) (74).…”
Section: Enhancing Biomacromolecules Stabilitymentioning
confidence: 72%
See 2 more Smart Citations
“…Our study revealed that there exists an exclusive synergistic stability effect of both the biomolecule guest and MOF host, enabled from the unique, new coordination bonds between the host and guest molecules ( Fig. 4C) (74).…”
Section: Enhancing Biomacromolecules Stabilitymentioning
confidence: 72%
“…One substantial drawback of this approach is that biomolecules significantly larger than the pore size of the host could not be encapsulated. To address this challenge, a number of recent works focus on exploiting biomolecules' intrinsic ability to initiate an in situ growth of MOFs and end up encapsulated in the framework analogs to natural biomineralization process (70)(71)(72)(73)(74). In this approach, biomolecules are situated inside the MOFs by generating macromolecular defects during MOF crystallization, which eliminates the pore size limitation of the presynthesized MOFs.…”
Section: Exogenous Bioaugmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Av ery recent and emerging application is the engineering of rigid MOF layers as exoskeleton to protect fragile biomacromolecules,i ncluding enzymes,t hrough ad e novo embedding strategy. [10][11][12][13][14][15] In this approach, biomacromolecules of different size and even viruses and cells were encased within MOFs that possessed significantly smaller pore dimensions than themselves. [15][16][17][18][19] It was demonstrated that the porous MOF exoskeletons could not only improve the stability of the encapsulated enzymes through structural confinement, but also allow selective transport of the guest via the accessible micropores network of the exoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…These appealing features allowed MOFs to evolve as an outstanding platform for gas separation, catalysis, drug delivery and sensing . A very recent and emerging application is the engineering of rigid MOF layers as exoskeleton to protect fragile biomacromolecules, including enzymes, through a de novo embedding strategy . In this approach, biomacromolecules of different size and even viruses and cells were encased within MOFs that possessed significantly smaller pore dimensions than themselves .…”
Section: Introductionmentioning
confidence: 99%